Research Thrusts in Small Firm Strategic Planning - Robinson, Richard B.; Pearce, John A. (Academy of Management Review, 1984)
Viewed historically, strategic planning research in small firms has emerged sporadically rather than in clear research tracks. This paper reviews over 50 planning-related studies from small firm settings. Four major research thrusts are identified from this literature. Key issues and findings associated with each thrust are summarized, and future research guidelines are derived.